Theoretical Aspects of Evaluating the Relationship between Traditional, Electronic and Multi-channel Sales Approaches and Results - Piatkovskytė, Gytė; Ulbinaitė, Aurelija (Information & Media, 2018)
[full article and abstract in Lithuanian; abstract in English] Companies are now operating in a globalized era, with constantly developing and rapidly growing information and communication technologies, with many transformations in communication forms and with intellectual capital- and knowledge-based competition aspects. Due to this, the choice of sales approaches is an essential part of the sales process, which determines the performance results, measured in terms of the efficiency of the companies, cooperation, market share, and other indicators. Before making decisions regarding the choice of the sales approach with which the end-user will be reached, or before making the decision to change the approach of sales, or after such a change, it is necessary for companies to assess the detailed impact thereof on their performance. This article highlights a holistic approach to decision-making related to the importance of choosing or modifying sales approaches, the importance of assessing the relationship between sales approaches and multi-threaded results on the needs of the market and operational efficiency, on the need of better access to markets and consumers, and successful business activities. After a systematic comparative analysis of the scientific literature, the theoretical model, which allows for estimating the relationship between business results and sales approaches through which end-users are reached, was created. The model was designed to rationalize the choices available when choosing the sales approaches. The relationship between sales approaches and results highlights the need for estimating qualitative variables, such as consumers, because they directly determine the company’s quantitative performance by purchasing the product offered by the company. The theoretical model helps systematically see the whole complex assessment process and, in each case, depending on the purpose of the assessment, to choose the methods which will let achieve the best results of the evaluation, at the same time allowing the company an opportunity to choose the best selling approach that would meet their expectations. It is necessary to pay attention to the fact that evaluation is a continuous process, so after the results of the evaluation of the chosen sales approach are received, it is necessary to return to the decision-making process and evaluate if the originally set goal was reached.